Scientometric review of smart water management literature from the sustainable development goal perspective - Bao, Fengyu; Martek, Igor; Wu, Qihong; Wang, Zhongqing; Yang, Yang; Chen, Chuan; Chan, Albert P. C. (International Journal of Strategic Property Management, 2023)
Water is essential to human survival; however, many people, particularly those in poorer countries, lack access to reliable sources of clean and safe water. Despite decades of effort to address this issue, water sustainability remains elusive even today. Smart technologies have been widely adopted for water management, rendering smart water management a promising path to achieving water sustainability. Nevertheless, the efficacy of such smart water management in attaining sustainability remains unclear. This study aims to investigate the progress made in pursuing water sustainability with smart water management through a scientometric literature review. The Scopus database was employed to extract a pool of 460 candidate publications, which were then analyzed for content using bibliometric analysis and VOSviewer software. Nine clustered research themes were classified, corresponding to the nine targets of sustainable development goals (SDGs) for water. The findings show that engagement across these topics is highly unequal, providing substantial guidance on where emerging research efforts should be concentrated. The novelty of this study mainly lies in the SDG perspective that provides a significant but overlooked angle for observing progress in smart water management domain. The findings can enlighten the international water industry to create a more favorable environment for regions lagging in using smart technologies to facilitate overall water sustainability.